Electrode composition, method for producing same, electrode slurry, electrode, and lithium secondary battery
By using a binder made of linear polymer in the electrode composition and adjusting its pH, the problem of hydrogen production in the silicon-based compound electrode composition is solved, reducing the risk of explosion and improving the capacity retention rate of the battery.
Patent Information
- Application Number
- CN202380048220.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-15
- Filing Date
- 2023-12-18
- Publication Date
- 2025-02-28
AI Technical Summary
During the preparation and storage of the electrode composition or slurry containing silicon-based compounds, hydrogen may be generated due to the surface oxidation reaction, resulting in a reduced risk of explosion and phase stability.
The production of hydrogen is reduced by using a binder composed of linear polymers in the electrode composition and adjusting its pH value in the range of 5 to 7.
The risk of explosion caused by hydrogen production is effectively reduced and the phase stability of the electrode composition is improved, thereby achieving excellent capacity retention in lithium secondary batteries.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[0001] This application claims priority to and the benefit of Korean Patent Application Nos. 10-2022-0184163 and 10-2023-0182639 filed on December 26, 2022 and December 15, 2023, respectively, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field
[0002] The present application relates to an electrode composition, a preparation method thereof, an electrode slurry, an electrode and a lithium secondary battery. Background Art
[0003] Due to the rapid growth in the use of fossil fuels, the demand for the use of alternative energy or clean energy is increasing, and as part of this trend, the most actively researched field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their use fields are increasing.
[0005] With the technological development and increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for preparing high-density electrodes with high energy density per unit volume have been actively studied.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.
[0007] In particular, recently, in response to the demand for high-density energy batteries, a method of increasing capacity by using a silicon-based compound (e.g., Si / C or SiOx) having a capacity 10 times that of a graphite-based material as a negative electrode active material has been actively studied. Although the silicon-based compound as a high-capacity material has an advantage of large capacity compared to graphite used in the related art, there is a problem that during the preparation and storage of an electrode composition or slurry containing the silicon-based compound, hydrogen may be generated due to a surface oxidation reaction, resulting in an explosion risk and reduced phase stability.
[0008] In order to solve this problem, various methods have been discussed, but in the case of these methods, the performance of the battery may be deteriorated instead, so that there is still a limitation in the commercialization of the manufacture of negative electrode batteries including silicon-based compounds.
[0009] Therefore, additional research on binders that can reduce hydrogen generation from silicon-based compounds is needed to improve the above issues while maintaining battery performance. Summary of the invention
[0010] [Technical issues]
[0011] In order to solve this problem, the present application is directed to providing an electrode composition that adjusts hydrogen ion concentration (pH) and includes a binder in a specific form, a preparation method thereof, an electrode slurry, an electrode, and a lithium secondary battery.
[0012] [Technical solution]
[0013] An exemplary embodiment of the present specification provides an electrode composition including: an electrode active material; a conductive material; and a binder, wherein the binder is composed of a linear polymer and has a pH of 5 or more and 7 or less when measured at 25°C.
[0014] Another exemplary embodiment provides an electrode slurry including the electrode composition and a solvent.
[0015] Another exemplary embodiment provides an electrode including: an electrode current collector layer; and an electrode active material layer, wherein the electrode slurry is applied on one surface or both surfaces of the electrode current collector layer.
[0016] Yet another exemplary embodiment provides a lithium secondary battery including: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the above-mentioned electrode.
[0017] Finally, a method for preparing an electrode composition is provided, the method comprising: preparing a binder; adjusting the pH of the binder to a range of greater than 5 and less than 7 using a base when measured at 25°C; and adding an electrode active material and a conductive material thereto and mixing the resulting mixture, thereby preparing the electrode composition.
[0018] [Beneficial Effects]
[0019] The electrode composition of the exemplary embodiment of the present invention makes the form of the binder composed of a linear polymer and adjusts the hydrogen ion concentration (pH) of the binder itself, thereby being able to provide an effect of preventing the generation of hydrogen due to surface oxidation reaction during the preparation and storage of the electrode composition (or electrode slurry containing a solvent). As a result, the electrode composition (or electrode slurry) containing the binder can effectively reduce the risk of explosion caused by the generation of hydrogen. In addition, by improving the phase stability of the electrode composition, when it is used in a lithium secondary battery, the electrode composition leads to an excellent capacity retention rate.
[0020] The method of preparing an electrode composition according to another exemplary embodiment of the present invention can further ensure process stability, safety, etc. because the electrode composition having the above-mentioned characteristics is used. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a photograph of a state of an electrode including the electrode composition according to an exemplary embodiment of the present application after being stored for a period of time.
[0022] Figure 2 is a photograph of the state of an electrode including an electrode composition in the prior art after being stored for a period of time. DETAILED DESCRIPTION
[0023] Before describing the present invention, some terms are first defined.
[0024] When a component “comprises” a constituent element in the present specification, unless otherwise specifically described, this does not mean that other constituent elements are excluded but means that other constituent elements may be further included.
[0025] In this specification, "p to q" means a range of "p or more and q or less".
[0026] In the present specification, the fact that a polymer includes a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, it is interpreted as the same as when the polymer includes a monomer as a monomer unit.
[0027] In this specification, "polymer" should be understood to be used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".
[0028] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene conversion molecular weights measured by measuring molecular weight using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees as standard materials by gel permeation chromatography (GPC). In this specification, unless otherwise specified, molecular weight refers to weight average molecular weight.
[0029] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that a person skilled in the art to which the present invention pertains can easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to the following description.
[0030] <Electrode composition>
[0031] An exemplary embodiment of the present specification is characterized in that a binder of an electrode composition is composed of a linear polymer, and pH of the binder is controlled to be 5 or more and 7 or less when measured at 25°C.
[0032] In the electrode composition of the exemplary embodiment, since the binder is composed of a linear polymer, direct contact with the electrode active material is promoted, so that the content of the conductive material can be relatively reduced, because the conductivity can be further improved, thereby increasing the content of the electrode active material. In addition, compared with when the binder is composed of a cyclic polymer or contains a cyclic polymer, the dispersibility (especially water dispersibility) can be effectively improved. In addition, by adjusting the pH of the binder to improve the bonding strength of the binder and preventing the bonding between the electrode active material and / or the conductive material from loosening during repeated charging / discharging, the electrode composition containing the binder can improve the future stability of the electrode or lithium secondary battery. In addition, according to the exemplary embodiment, by adjusting the pH of the binder itself, the following effect can be provided: during the preparation and storage of the electrode composition containing the binder and the electrode slurry containing it, the amount of hydrogen generated due to the surface oxidation reaction is significantly reduced.
[0033] In this specification, the pH may be measured using a known pH meter, for example, a pH meter SD20 manufactured by Mettler-toledo Co., Ltd. may be used.
[0034] As a pH adjustment method, a known method is used, but preferably the concentration (e.g., molar concentration (M)) of a strong base (e.g., NaOH or KOH), a weak base (e.g., ammonium hydroxide), a strong acid (e.g., HCl), or a weak acid (e.g., acetic acid) can be adjusted and the acid or base can be added dropwise to the adhesive using a pH meter until the desired pH is reached.
[0035] In the present specification, the pH of the binder itself is in the range of 5 to 7, but the pH of the electrode composition including the binder may be slightly outside the range of 5 to 7. For example, the pH of the electrode composition may be 5 to 8, preferably 5 to 7.5, but is not limited thereto.
[0036] In the exemplary embodiment of the present specification, the binder includes a first monomer and a second monomer, the first monomer is (meth)acrylic acid, and the second monomer may be (meth)acrylamide, (meth)acrylonitrile, or a combination thereof.
[0037] In the electrode composition of the exemplary embodiment, the binder may exhibit hydrophilicity, which is necessary as an aqueous binder in the future. In addition, when the electrode composition including the binder is used in a lithium secondary battery, the binder is used by making the binder have a property that makes it difficult to dissolve in the electrolyte in the lithium secondary battery, and strong stress or tensile strength can be imparted. In particular, when a silicon-based active material is included in the electrode composition, problems caused by volume expansion and contraction of the silicon-based active material during charging and discharging can be effectively suppressed.
[0038] In the present specification, the term "(meth)acrylic" may mean methacrylic and / or acrylic.
[0039] In the exemplary embodiment of the present specification, a molar ratio of the first monomer to the second monomer may be 2:8 to 8:2, preferably 3:7 to 7:3.
[0040] Since the electrode composition according to the exemplary embodiment satisfies the above-mentioned molar ratio, water dispersibility may be further improved, and lifespan performance may be further improved.
[0041] In the exemplary embodiment of the present specification, the content of the electrode active material may be 60 parts by weight or more based on 100 parts by weight of the electrode composition.
[0042] In another exemplary embodiment of the present specification, the content of the electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, based on 100 parts by weight of the electrode composition.
[0043] In the exemplary embodiment of the present specification, the electrode active material may include one or more selected from the group consisting of a silicon-based active material and a carbon-based active material.
[0044] In another exemplary embodiment of the present specification, the electrode active material may be composed of a silicon-based active material and a carbon-based active material.
[0045] In the present specification, the capacity of the silicon-based active material is 10 times that of the carbon-based active material, and therefore, when the silicon-based active material is applied to an electrode, especially a negative electrode, an electrode with a higher level of energy density can be achieved, even with a thinner thickness than when only the carbon-based active material is included.
[0046] In another exemplary embodiment of the present specification, when the electrode active material consists of a silicon-based active material and a carbon-based active material, a composition ratio between the silicon-based active material and the carbon-based active material may be 2:98 to 30:70.
[0047] The electrode active material of the exemplary embodiment includes a carbon-based active material as a main component, and thus can further provide the following effects: slight expansion occurs during charge and discharge due to small volume expansion of the active material, and the conductivity of the electrode is excellent.
[0048] In another exemplary embodiment of the present specification, the electrode composition refers to a negative electrode composition, and thus, an electrode active material, a conductive material, and a binder are all used for the negative electrode composition and may be referred to as a negative electrode active material, a negative electrode conductive material, and a negative electrode binder, respectively.
[0049] The electrode composition (specifically, the negative electrode composition) of the exemplary embodiment has the following characteristics: by using the electrode active material within the above range, using a specific conductive material, and a specific binder capable of suppressing the volume expansion rate during charging and discharging, even when using the electrode active material within the above range, the performance of the negative electrode does not deteriorate, and the output characteristics during charging and discharging are excellent.
[0050] In the exemplary embodiment of the present specification, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.
[0051] In the exemplary embodiment of the present specification, the electrode active material includes a silicon-based active material, and the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, it may include 70 parts by weight or more of SiOx (x = 0).
[0052] In the exemplary embodiment of the present application, for the silicon-based active material, only pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on a total of 100 parts by weight of the silicon-based active material as described above, the above range includes pure Si particles (SiOx (x = 0)) that are not combined with other particles or elements.
[0053] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the silicon-based active material may include 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, or 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less of SiOx (x = 0).
[0054] In the present specification, although there is a large amount of silicon-based active material, the electrode composition containing the silicon-based active material within the above content range is still meaningful because by adjusting the pH of the binder, the amount of hydrogen gas generated by the silicon-based active material is very small.
[0055] In the present specification, the silicon-based active material may exist, for example, in a crystalline or amorphous form. Specifically, the silicon particles of the silicon-based active material may preferably be spherical particles, but are not limited thereto.
[0056] In the present specification, the case of SiO2 where x is 2 in SiOx is not included because this SiO2 does not react with lithium ions and thus cannot store lithium. Therefore, it is preferred that x falls within the range of the exemplary embodiment.
[0057] In this specification, the silicon-based active material may be Si / C composed of a composite of Si and C, or Si.
[0058] In the present specification, two or more silicon-based active materials may be mixed and used.
[0059] In the exemplary embodiment of the present specification, the carbon-based active material may include one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
[0060] In the exemplary embodiment of the present specification, the content of the conductive material may be 0.03 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the electrode composition.
[0061] In another exemplary embodiment of the present specification, the content of the conductive material may be 0.03 parts by weight or more and 40 parts by weight or less, preferably 0.05 parts by weight or more and 30 parts by weight or less, and more preferably 0.5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the electrode composition.
[0062] In the exemplary embodiment of the present application, the conductive material may include one or more selected from the group consisting of a dot-shaped conductive material, a plane-shaped conductive material, and a line-shaped conductive material.
[0063] In the exemplary embodiment of the present specification, the conductive material may include a dot-shaped conductive material and a line-shaped conductive material.
[0064] In this specification, the point-shaped conductive material can be used to enhance the conductivity of the negative electrode, and refers to a point-shaped or spherical conductive material having conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and can preferably include carbon black and / or artificial graphite in terms of achieving high conductivity and excellent dispersibility.
[0065] In this specification, the planar conductive material can increase the surface contact between the silicon particles in the negative electrode to improve the conductivity and simultaneously suppress the disconnection of the conductive path due to volume expansion. The planar conductive material can be expressed as a plate-like conductive material or a block-like conductive material. Examples of planar conductive materials can include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite sheets, and can preferably be plate-like graphite.
[0066] In the present specification, the linear conductive material may be a carbon nanotube. The carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or a rope, in which a plurality of carbon nanotube units are arranged side by side or entangled, and in this arrangement, the longitudinal axes of the carbon nanotube units are substantially the same. In the carbon nanotube unit, the graphene sheet has a cylindrical shape with a nanometer-sized diameter and has a sp 2 In this case, the carbon nanotube unit can exhibit the characteristics of a conductor or a semiconductor, depending on the structure and angle of the rolled graphite sheet. Compared with tangled carbon nanotubes, bundled carbon nanotubes can be evenly dispersed during the preparation of the negative electrode, and can improve the conductivity of the negative electrode by smoothly forming a conductive network in the negative electrode.
[0067] In another exemplary embodiment of the present specification, the conductive material may be a negative electrode conductive material.
[0068] In this specification, the negative electrode conductive material is applied to the negative electrode and has a completely different configuration from the positive electrode conductive material applied to the positive electrode. In other words, the negative electrode conductive material is used to capture the contact points between the silicon-based active material (the volume expansion of the electrode is very large due to charging and discharging), while the positive electrode conductive material is used to impart partial conductivity and play a buffering role during rolling, so the negative electrode conductive material and the positive electrode conductive material have different structures and functions.
[0069] In the exemplary embodiment of the present application, the content of the binder may be 2 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the electrode composition.
[0070] In another exemplary embodiment of the present specification, the content of the binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, or may be 2 parts by weight or more, 5 parts by weight or more, and 10 parts by weight or more, based on 100 parts by weight of the electrode composition.
[0071] In another exemplary embodiment of the present specification, the binder may be a negative electrode binder.
[0072] In the exemplary embodiment of the present specification, the weight average molecular weight of the binder may be 100,000 g / mol or more and 1,500,000 g / mol or less.
[0073] The electrode composition of the exemplary embodiment is characterized in that, because the weight average molecular weight of the binder satisfies the above range, the mechanical strength is excellent, and because the interaction between the molecules is high, the bonding strength of the electrode is excellent. In addition, when the above range is met, the viscosity of the binder can be selected within an appropriate range so that when the negative electrode is manufactured using the binder, the electrode has excellent coatability.
[0074] In the exemplary embodiment of the present specification, the adhesive may be a water-based adhesive.
[0075] According to the exemplary embodiment, the following advantages can be further provided: when an aqueous binder is used in an electrode composition, dissolution is rapid, processability is promoted, and efficiency is high, and if an aqueous binder is used in an electrode slurry in the future, viscosity can be stably controlled, long-term circulation can be ensured, and high bonding strength can be exhibited under various operating temperature conditions.
[0076] In the present specification, a polymerization initiator is used to prepare an aqueous adhesive, and ammonium persulfate may be used as an example of the polymerization initiator, but the polymerization initiator is not limited thereto.
[0077] <Electrode slurry>
[0078] The exemplary embodiment of the present specification provides an electrode slurry including the above-mentioned electrode composition and a solvent.
[0079] In another exemplary embodiment of the present invention, the solvent may include those known in the art. For example, the solvent may be water (eg, distilled water) or NMP, but is not limited thereto.
[0080] The electrode slurry of the present invention is a negative electrode slurry, and therefore the electrode composition may involve the negative electrode slurry.
[0081] In some cases, when the viscosity of the electrode slurry is controlled within a suitable range by appropriately adjusting the average particle size (D50) of the silicon-based active material or the specific surface area of the particles, the dispersion of the components in the slurry (e.g., conductive material, binder, silicon-based active material, carbon-based active material, etc.) can be improved. Therefore, the contact area between the components is improved, so that the conductive network can be maintained, the capacity retention rate can be improved, and the current density non-uniformity during charge / discharge can also be prevented.
[0082] In addition, in some cases, the viscosity of the electrode slurry may be adjusted to 5000 cps to 6000 cps. When the above viscosity range is satisfied, storage properties are excellent, and when one or both surfaces of the electrode current collector layer are coated with the electrode slurry in the future, coating properties are excellent.
[0083] <Electrode>
[0084] An exemplary embodiment of the present specification provides an electrode including: an electrode current collector layer; and an electrode active material layer, wherein the electrode slurry is applied on one surface or both surfaces of the electrode current collector layer.
[0085] In another exemplary embodiment of the present specification, the electrode is a negative electrode, and therefore, the electrode current collector layer, the electrode slurry, and the electrode active material layer all relate to the negative electrode.
[0086] In this specification, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. The negative electrode current collector layer is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, and aluminum-cadmium alloys can be used. In addition, the negative electrode current collector layer may also form microscopic irregularities on its surface to increase the adhesion strength of the negative electrode active material. The negative electrode current collector layer can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0087] In another exemplary embodiment of the present specification, there is provided a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0088] However, the thickness may be variously changed according to the type and purpose of the negative electrode used, and is not limited thereto.
[0089] <Lithium Secondary Battery>
[0090] Battery>
[0091] An exemplary embodiment of the present specification provides a lithium secondary battery including: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the above-mentioned electrode.
[0092] Specifically, the lithium secondary battery according to the exemplary embodiment may include the above-described electrode.
[0093] Specifically, the first electrode may be a cathode and the second electrode may be a cathode, or the first electrode may be a cathode and the second electrode may be a cathode.
[0094] Specifically, the lithium secondary battery may include a negative electrode, a positive electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, and the negative electrode is the same as the negative electrode described above. Since the negative electrode has been described in detail, its detailed description will be omitted.
[0095] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material.
[0096] In the positive electrode, the positive electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver, etc., can be used. Moreover, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and microscopic irregularities can be formed on the surface of the collector to improve the adhesion of the positive electrode active material. The positive electrode collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0097] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound, such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide, such as LiFe3O4; a lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (where c1 is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B or Ga, c2 = 0.01 to 0.3) represented by Ni-type lithium nickel oxide; represented by the formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn or Ta, c3 = 0.01 to 0.1); LiMn2O4 in which a part of the Li atoms are replaced by alkaline earth metal ions; etc., but not limited thereto. The positive electrode can be lithium metal.
[0098] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0099] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the constituted battery. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.
[0100] Alternatively, the positive electrode binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0101] The separator separates the negative electrode from the positive electrode and provides a mobile path for lithium ions, and can be used without particular restriction, as long as it is generally used as a separator in a secondary battery, and in particular, a separator having excellent moisture retention ability to the electrolyte and low resistance to the movement of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof. Moreover, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a single layer or multilayer structure can be selectively used.
[0102] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes, which can be used to prepare lithium secondary batteries, but are not limited thereto.
[0103] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0104] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone (NMP), propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl pyrophosphate and ethyl propionate can be used.
[0105] In particular, among carbonate organic solvents, cyclic carbonates ethylene carbonate and propylene carbonate can be preferably used because these cyclic carbonates are high-viscosity organic solvents with high dielectric constants and thus dissociate lithium salts well, and such cyclic carbonates can be more preferably used because these cyclic carbonates can be mixed in an appropriate proportion with low-viscosity and low-dielectric-constant chain carbonates (e.g., dimethyl carbonate and diethyl carbonate) and used to prepare an electrolyte with high conductivity.
[0106] As the metal salt, a lithium salt can be used. The lithium salt is a substance that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN -and (CF3CF2SO2)2N - One or more of .
[0107] In the electrolyte, in order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be further included, for example, a halogenated alkylene carbonate compound (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.
[0108] An exemplary embodiment of the present invention provides a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include a lithium secondary battery having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0109] Figure 1 is a photograph of a state of an electrode including the electrode composition according to an exemplary embodiment of the present application after being stored for a period of time. Figure 2 is a photograph of an electrode comprising an electrode composition in the prior art after being stored for a period of time. Figure 1 and Figure 2 The storage time (about 24 hours) under high temperature conditions (about 60°C) is the same, but it can be confirmed that Figure 1 In the case of Figure 2 In the process, due to the large amount of hydrogen produced, expansion is serious.
[0110] <Method for preparing electrode composition>
[0111] In an exemplary embodiment of the present invention, there is provided a method for preparing the above-mentioned electrode composition, the method comprising: preparing a binder; adjusting the pH of the binder to a range of 5 or more and 7 or less when measured at 25° C. using a base; and adding an electrode active material and a conductive material thereto and mixing the resulting mixture to prepare the electrode composition. In this specification, the above contents apply to the binder, pH, electrode active material, conductive material, etc. herein.
[0112] Hereinafter, preferred embodiments will be presented to facilitate understanding of the present invention, but these embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and these changes and modifications naturally also fall within the scope of the appended claims.
[0113] Preparation Example. Preparation of water-based adhesive
[0114] <Preparation Example 1>
[0115] In a reactor equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inflow tube, acrylamide (50% aqueous solution) and acrylic acid (AA, 80% aqueous solution) were used and mixed in a molar ratio of 7:3, ammonium persulfate was added thereto as a polymerization initiator, and then the resulting mixture was reacted at 80° C. for 5 hours to prepare a water-based polymer (aqueous solution state).
[0116] Thereafter, a 0.1 mol / liter (M) sodium hydroxide aqueous solution was dropped into the water-based polymer to prepare a water-based polymer adhesive having a pH of 5.6.
[0117] <Preparation Example 2>
[0118] A water-based adhesive was prepared in the same manner as in Preparation Example 1, except that the water-based adhesive was prepared at pH = 6.6.
[0119] <Preparation Example 3>
[0120] A water-based adhesive was prepared in the same manner as in Preparation Example 1, except that acrylic acid (AA, 80% aqueous solution) and acrylonitrile (AN) were used and mixed at a molar ratio of 7:3 to prepare a water-based polymer, and then a water-based adhesive having a pH of 5.3 was prepared.
[0121] <Comparative Preparation Example 1>
[0122] A water-based adhesive was prepared in the same manner as in Preparation Example 1, except that the water-based adhesive was prepared at pH=8.0.
[0123] <Comparative Preparation Example 2>
[0124] A water-based adhesive was prepared in the same manner as in Preparation Example 3, except that the water-based adhesive was prepared at pH = 7.8.
[0125] <Comparative Preparation Example 3>
[0126] A water-based adhesive was prepared in the same manner as in Preparation Example 1, except that the water-based adhesive was prepared at pH = 4.0.
[0127] <Comparative Preparation Example 4>
[0128] An organic linear adhesive was prepared by mixing bicyclo[2,2,7]oct-2-ene-3,5,6,4-tetracarboxylic dianhydride (BCDA) and 4,10-oxydiphenylamine (ODA) in a NMP solvent at a molar ratio of 1:1 and reacting the resulting mixture at 180° C. for 4 hours. However, due to the characteristics of the organic adhesive, the pH needs to be measured under conditions different from those of other adhesives, and therefore an accurate pH value cannot be measured.
[0129] Example. Preparation of electrode slurry
[0130] <Example 1>
[0131] Si with d50 = 5.2 μm was used as the negative electrode active material, three types of conductive materials: carbon black (product name: Super C65, produced by TIMCALLtd.), artificial graphite (product name: SFG6L, produced by TIMCALLtd.) and SWCNT were used as conductive materials, the water-based binder of Preparation Example 1 was used as the binder, and the resulting mixture was mixed so that Si:C65:SFG6L:SWCNT:binder = 80:2:7.5:0.5:10 (weight ratio), thereby preparing an electrode composition.
[0132] Thereafter, water was added as a solvent, and the content of water was adjusted in consideration of coatability, viscosity, and solid content so that the viscosity of the electrode slurry was in the range of 5000 cps to 6000 cps.
[0133] <Example 2>
[0134] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Preparation Example 2 was used.
[0135] <Example 3>
[0136] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Preparation Example 3 was used.
[0137] <Example 4>
[0138] An electrode slurry was prepared in the same manner as in Example 1, except that a negative electrode active material of artificial graphite (QCG-N2, manufactured by Shanshan):Si=90:10 was used.
[0139] <Example 5>
[0140] An electrode slurry was prepared in the same manner as in Example 1, except that a negative electrode active material of artificial graphite:SiC (SD5100A, manufactured by Sila Nanotechnologies Inc.) = 85:15 was used.
[0141] <Comparative Example 1>
[0142] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Comparative Preparation Example 1 was used.
[0143] <Comparative Example 2>
[0144] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Comparative Preparation Example 2 was used.
[0145] <Comparative Example 3>
[0146] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Comparative Preparation Example 3 was used.
[0147] <Comparative Example 4>
[0148] An electrode slurry was prepared in the same manner as in Comparative Example 1, except that a negative electrode active material of artificial graphite:Si=90:10 was used.
[0149] <Comparative Example 5>
[0150] An electrode slurry was prepared in the same manner as in Comparative Example 1, except that a negative electrode active material of artificial graphite:SiC=85:15 was used.
[0151] <Comparative Example 6>
[0152] An electrode slurry was prepared in the same manner as in Example 1, except that the water-based binder of Comparative Preparation Example 4 was used.
[0153] Experimental example
[0154] <Experimental Example 1: Measurement of the Amount of H2 Gas Generated in Electrode Slurry>
[0155] 5 g of each electrode slurry of Examples 1 to 5 and Comparative Examples 1 to 6 was placed in a bag of 9 cm × 9 cm in size, the bag was sealed, and then left to stand in a constant temperature chamber at 60° C. for 24 hours. Next, the gas generated in the bag was captured, and the amount of H2 gas generated was quantitatively analyzed using GC / MS (7890B-5977B). The results are shown in Table 1 below.
[0156] <Experimental Example 2: Battery Manufacturing and Battery Characteristics Evaluation>
[0157] A copper foil with a thickness of 18 μm was coated with each electrode slurry and dried, an electrode active material layer with a thickness of 50 μm was formed on one surface of the copper foil, and the copper foil was punched into a circle with a diameter of 14 Φ (mm) to make a test electrode (negative electrode). A metal lithium foil with a thickness of 0.3 mm was used as a positive electrode. A porous polyethylene sheet with a thickness of 0.1 mm was used as a separator. In addition, the following electrolyte was used: LiPF6 as a lithium salt was dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of 1:1 at a concentration of about 1 mol / L.
[0158] The negative electrode, positive electrode, separator and electrolyte were sealed in a stainless steel container to manufacture a coin cell with a thickness of 2 mm and a diameter of 32 mm for evaluation. The coin cell was charged at a constant current of 0.05 C until the voltage reached 0.01 V, and discharged at a constant current of 0.05 C until the voltage reached 1.5 V to determine the discharge capacity and initial efficiency, and then, in the same voltage range as above, the capacity retention rate was tested at a constant current of 0.2 C to obtain the cycle characteristics, and the results are shown in Table 1 below.
[0159] [Table 1]
[0160]
[0161] As shown in Table 1, it can be seen that the battery (Examples 1 to 5) using the electrode slurry in which the pH of the binder satisfies the range of 5 to 7 produces less hydrogen than Comparative Examples 1 to 6, while having excellent cycle capacity retention. Specifically, in the case of Comparative Example 3 in which the pH of the binder is less than 5, the amount of hydrogen produced is low, but even if Si is used as the electrode active material, the capacity retention rate is very low. In addition, it can be seen that Comparative Examples 1, 2, 4 and 5 (in which the pH of the binder exceeds 7) are not suitable as binders even if the capacity retention rate is higher than 78%, because the amount of hydrogen produced is more than 34600 μL. In addition, it can be seen that Comparative Example 6 in which the binder is an organic binder is not suitable as a binder because even if the amount of hydrogen produced is low, the capacity retention rate is very low, at about 62%.
Claims
1. An electrode composition, comprising: an electrode active material; a conductive material; and a binder, in, wherein the binder consists of a linear polymer, and when measured at 25 °C, the pH of the binder is 5 or more and 7 or less.
2. The electrode composition according to claim 1, wherein The binder contains a first monomer and a second monomer, the first monomer is (meth)acrylic acid, the second monomer is (meth)acrylamide, (meth)acrylonitrile, or a combination thereof.
3. The electrode composition according to claim 2, wherein The molar ratio of the first monomer to the second monomer is 2:8 to 8:
2.
4. The electrode composition according to claim 1, wherein Based on 100 parts by weight of the electrode composition, the content of the electrode active material is 60 parts by weight or more.
5. The electrode composition according to claim 1, wherein The electrode active material includes one or more selected from the group consisting of a silicon-based active material and a carbon-based active material.
6. The electrode composition according to claim 5, wherein The silicon-based active material contains one or more selected from the group consisting of SiOx with x = 0, SiOx with 0 < x < 2, SiC, and Si alloy.
7. The electrode composition according to claim 5, wherein The electrode active material contains a silicon-based active material, the silicon-based active material contains one or more selected from the group consisting of SiOx with x = 0 and SiOx with 0 < x < 2, and based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of SiOx with x = 0.
8. The electrode composition according to claim 5, wherein The carbon-based active material includes one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
9. The electrode composition according to claim 1, wherein Based on 100 parts by weight of the electrode composition, the content of the conductive material is 0.03 parts by weight or more and 40 parts by weight or less.
10. The electrode composition according to claim 1, wherein The conductive material includes one or more selected from the group consisting of a dot-shaped conductive material, a planar conductive material, and a linear conductive material.
11. The electrode composition according to claim 1, wherein Based on 100 parts by weight of the electrode composition, the content of the binder is 2 parts by weight or more and 30 parts by weight or less.
12. The electrode composition according to claim 1, wherein The weight average molecular weight of the binder is 100,000 g / mol or more and 1,500,000 g / mol or less.
13. The electrode composition according to claim 1, wherein The binder is an aqueous binder.
14. An electrode paste, comprising the electrode composition according to any one of claims 1 to 13 and a solvent.
15. An electrode, comprising: an electrode current collector layer; and an electrode active material layer, wherein the electrode paste according to claim 14 is coated on one surface or both surfaces of the electrode current collector layer.
16. A lithium secondary battery, comprising: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the electrode according to claim 15.
17. A method for preparing an electrode composition, the method comprising: preparing a binder; when measured at 25 °C, adjusting the pH of the binder within a range of 5 or more and 7 or less using an alkali; and adding an electrode active material and a conductive material thereto and mixing the resulting mixture to prepare the electrode composition according to any one of claims 1 to 13.